Total flavonoids of Dracocephalum moldavica L. alleviate cognitive impairment via TNF-α/NF-κB p65 signaling pathway in vascular dementia rats - Ma, Shangjia; Jia, Jianxin; Wu, Lie; Tian, Kai; Wang, Lu; Li, Hua; Lv, Jiayu; Gao, Dewang; Yang, Zhanjun; Guo, Xia (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to elucidate the neuroprotective effects and underlying mechanisms of total flavonoids of Dracocephalum moldavica L. (TFDM) in VaD by using network pharmacology and in vivo validation.MethodsThe network pharmacology was used to explore the mechanism of TFDM to improve VaD. A rat model of VaD was established using permanent bilateral common carotid artery occlusion (2VO). The Morris water maze test assessed spatial learning and memory capacities. Nissl staining was used to examine the neuronal damage. Western blot and Immunofluorescence analysis was employed to evaluate protein levels of factors associated with neuroinflammation, blood-brain barrier integrity, and angiogenesis.ResultsThe network pharmacology suggests TFDM may combat VaD through TNF-α/NF-κB p65 signaling pathways. TFDM treatment may attenuate memory deficits associated with 2VO and reduce neuronal damage. TFDM improved blood-brain barrier integrity and promoted angiogenesis by downregulating MMP-9 and upregulating ZO-1 and VEGFA. Moreover, TFDM exhibited anti-inflammatory properties by inhibiting TNF-α and NF-κB p65 production, thereby mitigating the neuroinflammatory response in VaD rats.ConclusionTFDM demonstrated significant improvement in cognitive function in VaD rats. This improvement was attributed to the multifaceted effects, including the improvement of blood-brain barrier integrity, promotion of angiogenesis, and reduction of neuroinflammation. These findings suggest that TFDM may represent a promising therapeutic approach for VaD management.